HBR's 10 must reads on women and leadership - Sandberg, Sheryl; Hewlett, Sylvia Ann; Williams, Joan C.; Tannen, Deborah; Ibarra, Herminia; Beaulieu, Callie; Sarris, William (Gildan Audio, 2020)
What will it take to create a more gender-balanced workplace'We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you understand where gender equality is today-and how far we still have to go. This book will inspire you to: better understand the path women must take to leadership; learn the root causes of the barriers that exist for women in the workplace; check your own gender biases and distinguish between confidence and competence in your colleagues; manage a more effective gender-diversity program; recognize the issues women face when speaking up about bias or harassment; and help women reenter the workforce after taking time off-and create opportunities for them to reach their ambitions.